Design and implementation of a radio controlled led lighting system - Bálint Ádám; Sárosi József (2016)
Technological advances allow us to control LED (Light Emitting Diode) lighting at home, in the office it can even allow us to change the intensity of the light and this is just the beginning of what the future holds for us. In this study an LED internal lighting fixture of our own design will be presented focusing on each step in its design. Firstly, the features, types and history of LEDs will be presented, next the products available in market that are required for the completion of the device. Finally, the design and implementation as well as the radio frequency controlled LED indoor lighting fixture will be shown.